Testicular structure and description of the seminal pathway in Leporinus macrocephalus (Anostomidae, Teleostei) - Munoz, Mario Esteban [UNESP]; Batlouni, Sergio Ricardo [UNESP]; Franceschini Vicentini, Irene Bastos [UNESP]; Vicentini, Carlos Alberto [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
The present study examined the testicular structure and the seminal pathway in freshwater fish Leporinus macrocephalus (Garavello and Britski, 1988). Twenty-five specimens of this species were studied. Testicular structure was analyzed using light and transmission electron microscopy. The testicular main ducts were examined by means of conventional histology, corrosion-cast technique and scanning electron microscopy. Additional techniques were applied for polysaccharides histochemistry and immunohistochemistry for androgen receptor. The testicular parenchyma was classified as the anastomosing tubular testis type with spermatogonia occurring along the lengths of the seminiferous tubules. The seminiferous tubules emptied directly into the testicular main ducts. The wall of the testicular main ducts in L macrocephalus consisted of three layers: epithelium, connective tissue and peritoneum. The epithelium changed from simple cuboidal to pseudostratified. The histochemical analysis revealed the presence of granules PAS positive in the epithelial cells. The immunoreactivity to androgen receptor was noted in the testicular main ducts through all cytoplasmic areas of epithelial cells. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Testicular structure; Testicular main ducts; Morphology; Teleost fish